2007
DOI: 10.1038/sj.mp.4002080
|View full text |Cite
|
Sign up to set email alerts
|

An association screen of myelin-related genes implicates the chromosome 22q11 PIK4CA gene in schizophrenia

Abstract: Several lines of evidence, including expression analyses, brain imaging and genetic studies suggest that the integrity of myelin is disturbed in schizophrenia patients. In this study, we first reconstructed a pathway of 138 myelin-related genes, all involved in myelin structure, composition, development or maintenance. Then we performed a two-stage association analysis on these 138 genes using 771 single nucleotide polymorphisms (SNPs). Analysis of our data from 310 cases vs 880 controls demonstrated associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
3
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 55 publications
5
89
3
1
Order By: Relevance
“…We found no support for rs165793, the most strongly associated SNP reported earlier in 22q11.2DS (P ¼ 1 for psychosis, P ¼ 0.71 for schizophrenia) or for the SNPs showing strongest evidence in the population studies [Jungerius et al, 2008;International Schizophrenia Consortium et al, 2009] (Table I). The earlier studies could not formally distinguish between an effect driven primarily by haplotypes or by single SNPs; in the present study, we obtained no support for haplotype association (permutation P ¼ 0.99 and 0.95 for psychosis and schizophrenia, respectively).…”
contrasting
confidence: 45%
“…We found no support for rs165793, the most strongly associated SNP reported earlier in 22q11.2DS (P ¼ 1 for psychosis, P ¼ 0.71 for schizophrenia) or for the SNPs showing strongest evidence in the population studies [Jungerius et al, 2008;International Schizophrenia Consortium et al, 2009] (Table I). The earlier studies could not formally distinguish between an effect driven primarily by haplotypes or by single SNPs; in the present study, we obtained no support for haplotype association (permutation P ¼ 0.99 and 0.95 for psychosis and schizophrenia, respectively).…”
contrasting
confidence: 45%
“…Similar phenotypic findings and interactions between the COMT genotype and proline levels were also found by Vorstman et al (Vorstman et al 2009b) but the association between high proline levels and lower IQ was not replicated. In a study of 79 Caucasian adults with 22q11.2DS, 37 with schizophrenia, Vorstman et al (Vorstman et al 2009a) found significant association to the same rs165793-G allele of the PIK4CA gene as in a general population sample of schizophrenia (Jungerius et al 2008). Although a meta-analysis that included an independent study of 20 subjects with 22q11.2DS and psychotic disorders was nominally significant, the results did not confirm a large effect size for this variant (Ikeda et al 2010).…”
Section: The Mouse As a Model For Dissecting The 22q112 Chromosomal mentioning
confidence: 75%
“…However, a general population sample of schizophrenia showed no association to TBX1 [34]. Three SNPs in the PIK4CA gene showed significant association (odds ratio 1.54; 95% CI, 1.28-1.86) to schizophrenia in a Dutch case-control study of 138 genes corrected for multiple testing [35]. All studies need replication.…”
Section: Linkage and Association Studiesmentioning
confidence: 99%